Ukuran Kantor Akuntan Publik (KAP), Opini Auditor, Financial Distress, dan Pergantian Manajer pada Auditor Switching - Devi Tiara Putri; Nursiam Nursiam (Perspektif Akuntansi, 2021)
The study aims to determine the effect of the size of Public Accounting Firm (KAP), Audit Opinion, Financial Distress, and Change of Manager in real estate and property companies listed in the Indonesia Stock Exchange (BEI) for the 2017-2019 period. The data used are secondary. The total sample from the observation is 123 sample obtained with the purposive sampling method. The research used logistic regression analysis techniques. The result of this research indicate that the size of the Public Accounting Firm (KAP) , Financial Distress, Change of Manager had no effect on auditor switching, and Audit Opinion affect on auditor switching